The Role of NGII in Disaster Management and Mitigation Program (Journal on Geoinformatics, Nepal, 2008)
Disaster is a sudden, accidental event that causes many deaths and injuries. Spatial data and related technologies such as Geographical Information System (GIS), Global Positioning System (GPS), remote sensing, have proven to be crucial for disaster management in such a way that without spatial data, one can not expect effective and ef! cient disaster management Although spatial data can facilitate disaster management, there are substantial problems with collection, access, dissemination and usage of required spatial data for disaster management. If each of the involved organizations in disaster management community collects some part of required spatial data for disaster response during their everyday business and emergency situation, required spatial data will be available to all participants. Sharing information between involved parties in order to facilitate coordinated disaster response operations is another challenge in disaster management. This includes the development of a prototype web-based system which can facilitate sharing, access and use of data in disaster management and especially disaster response. Geospatial data are the initial input for GIS and Emergency Response Modeling and Simulation Systems. In an emergency situation, different organizations become involved in disaster response. Survey Department, along with several other departments of Government of Nepal, jointly conducted several studies related to different types of disasters and their impacts. Survey Department has taken a lead in the creation of a National Geographic Information Infrastructure (NGII) in Nepal to share Geographic information. The mission of the programme is to strengthen planning and resources management through the development of geographic information infrastructure for the access of Geographic and attribute data for planning and decision making. Access to metadata information for all available geographic and related data could only assist in such initiatives.